A High-linearity CMOS Temperature Sensor Using a PTAT-voltage Driving Common-source Amplifier with a Source Resistor. (2015) - Jung, Ying-Zong; Wang, Ruey-Lue; Tsai, Hann-Huei; Liao, Hsin-Hao; Hao, Yi-Fan; Shi, Jian-Liang; Wu, Wey-De; Yu, Chi
Abstract: In this paper, a CMOS temperature sensor with a highly linear proportional-to-absolute-temperature (PTAT) output current, which results from a PTAT-voltage driving common-source amplifier with a source resistor, is presented. The second-order temperature coefficients of the PTAT voltage and the resistance of polysilicon and diffused-silicon resistors are all positive and hence the resulting current exhibits high linearity of at least 99.999% from 0 to 100 °C. With a silicided p-type polysilicon source resistor, the simulated and measured temperature characteristics of pulse frequencies exhibit sensitivities of 424 and 512 Hz/°C with linearities of 99.996% and 99.993%, respectively.